“Vamos brincar de gatinho?”: lesbianidades em Eu sou uma lésbica, de Cassandra Rios - Morais, Paula Lais Pombo de (2023)
In this dissertation, we aim to investigate lesbianities from the novel Eu sou uma lesbica, by the São Paulo writer Cassandra Rios, understanding that her literature was essential and pioneering in dealing with lesbianism while Brazil was experiencing a repressive period surrounded by taboos as a result of the Military dictatorship. For this, it was necessary to emphasize the writing and relevance of Rios in Brazilian literature, since Odette Rios Perez Gonzáles Hernândez Arellano (1932-2002) was significant, especially for having been resistant in approaching and discussing the lesbian theme and the figure of the sexually active woman in fiction. In this sense, we also deal with literati who, like Cassandra Rios, suffered censorship of their writings, because they brought up themes that were not easily digested by the patriarchal society. In addition, we discussed the nuances of Brazilian lesbian literature, taking as a starting point O cortiço (1890), by Aluízio de Azevedo – to talk about the first appearances of lesbian characters, ending in Amora (2015), by Natália Borges Polesso – to argue about of contemporary representations. We discussed excerpts from the silencing and rescue of Brazilian lesbian literature, considering the observations of Rodolfo Londero (2016) about the censorship that was established, mainly on the works of Rios and Carraro due to the “moral values” established by heteronormative society. From this, we were able to reflect on the multiple lesbian identities, understanding that there is no manual for lesbianity, as Tânia Navarro Swain (2004) points out. And it is precisely from this perception, of the diversity of lesbian existences, that we understand that the debate on the inscription of binarity on the lesbian and/or the lesbian is fundamental for the conception of different lesbian experiences. Finally, we deal with the lust (erotic desire) between lesbians and/or dykes as intrinsic aspects of the lesbian condition, which is evidenced from Rios' narrative, between Flávia and Kênia, as well as we discuss the invisibility to which homoaffective relationships are submitted. However, lesbian existences contest and resist heteronormativity based on the understanding that the lesbian and/or dyke is neither a man, nor a woman, nor a product of nature (WITTIG, 2019). Thus, the study of lesbian identities and existences allowed us to elaborate a reflection on diversity in lesbianity, as we understand the importance of resistance in terms of the defense of lesbian identity in its different manifestations, which breaks with the heterosexual logic and with the binary system on her body and her sexuality.